Policies and laws in the application of renewable energy Indonesia: A reviews - Erdiwansyah, .; Asri, Gani; Nurdin, M. H.; Rizalman, Mamat; R. E., Sarjono (AIMS Press, 2022)
Renewable energy is a global energy system that is very important in nature and humans' harmonious and conducive development. Considerable attention from the government towards renewable energy is due to the increasing energy demand. The impact of the current energy shortage has also resulted in damage to the environment. The current legal framework for accelerating the development of renewable energy has made a considerable contribution but is still not in favor of investors. Thus, the integration of renewable energy into the national energy system is still far from being expected, so the cooperation between the government and industrial development must be further enhanced. The specific aim of this work is to adopt various practices and policies towards the development of renewable energy from several developing countries. A critical review of this work will discuss policies and legislation on renewable energy policies especially under-operation, fragmentation, and obsolescence. Policies in favor of renewable energy developers are also presented in this paper. This paper as a whole investigates various renewable energy development policies from developing countries to be adopted in ensuring the availability of energy security in the future.